Quality of life after scoliosis surgery: the Hospital Sultanah Bahiyah experience - Karthikesan, Kishanraj (2021)
Introduction Idiopathic scoliosis is a is a complex three-dimensional deformity of the spinal column. Adolescent idiopathic scoliosis (AIS) is the most common type affecting healthy young individuals. Psychological well-being of these young group of patients has been area of concern when managing these patients. Aim of this study is to assess quality of life in patient undergoing corrective surgery for AIS using the SRS-30 questionaire. Methodology A cross sectional study of all patients that underwent deformity correction surgery for AIS from January 2016 till December 2019 in Hospital Sultanah Bahiyah was done. Patient had to be followed up for at least 6 months. Only patient with idiopathic adolescent scoliosis were included. Radiographic measurements of the cobb angle preoperative and postoperatively were obtained from medical records of the patient. Patients were then contacted and given the SRS-30 questionnaire to be filled up. Results 24 patients were recruited in this study based on the inclusion and exclusion criteria . The median preoperative Cobb angle was 63.0 (19.90), while post operatively it was 18.0 (11.25) with a percentage of correction of 68.0 (17.5). The average total SRS score is 4.20(0.38). Using the Spearman’s Rho correlation analysis there was a significance and moderately positive correlation between the satisfaction with management domain scores and the percentage of Cobb’s Angle correction. However, the total scores despite having a positive correlation, were not statisitcally significant. Conclusion In this study, the average total SRS score was 4.2(0.38) indicating a favourable outcome in terms of quality of life in patient undergoing scoliosis surgery in Hospital Sultanah Bahiyah.